2014
DOI: 10.4238/2014.october.20.7
|View full text |Cite
|
Sign up to set email alerts
|

Intermedin protects against myocardial ischemia-reperfusion injury in hyperlipidemia rats

Abstract: ABSTRACT. Hyperlipidemia is a well-established risk factor for the development of coronary atherosclerosis, while intermedin (IMD) has been identified as a novel calcitonin/calcitonin gene-related peptide family member involved in cardiovascular protection. However, whether IMD protects against hyperlipidemia-associated myocardial ischemia/reperfusion (MI/R) injury is unknown. We established a hyperlipidemia model using Sprague-Dawley rats, and created a MI/R condition by ligating the cardiac left circumflex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Moreover, IMD 1–53 treatment reversed Hcy-activated TGF- β 1 expression in the ApoE-/- mouse myocardium and in CFs. These anti-inflammatory effects of IMD were identical to the other researches for diabetes, hyperlipidemia, and hypertension 32, 34, 35) . It was reported that NF- κ B and JNK signal pathway played significant roles in proinflammatory process.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, IMD 1–53 treatment reversed Hcy-activated TGF- β 1 expression in the ApoE-/- mouse myocardium and in CFs. These anti-inflammatory effects of IMD were identical to the other researches for diabetes, hyperlipidemia, and hypertension 32, 34, 35) . It was reported that NF- κ B and JNK signal pathway played significant roles in proinflammatory process.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, IMD 1–53 can protect against myocardial ischemia injury and vascular smooth muscle cell calcification by attenuating ERS 30, 31) . IMD can inhibit inflammation in diabetic and hyperlipidemia rats and rats with salt-sensitive hypertension 3234) . However, whether IMD prevents myocardial fibrosis by inhibiting ERS and inflammation induced by Hcy in ApoE-/- mice has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…ADM2/IMD 1–53 protects cardiomyocytes against I/R‐induced injury by inhibiting ER stress, oxidative stress and apoptosis in a PI3K/Akt‐ and ERK‐dependent pathway (Song et al , ; Teng et al , ; Zhao et al , ). In isolated hearts, ADM2/IMD 1–40 , ADM2/IMD 1–47 and ADM2/IMD 1–53 ameliorated the I/R‐induced myocardial injury and decreased cardiac function (Yang et al , ). Further studies have shown that ADM2/IMD 1–47 protects cardiomyocytes and cardiac microvascular endothelium from I/R‐induced injury via AM 1 receptors (Bell et al , ; Bell et al , ).…”
Section: Adm2 and Cardiometabolic Diseasesmentioning
confidence: 99%
“…Whole protein extracts were obtained by homogenizing ventricle samples that were flash-frozen in liquid nitrogen in whole cell lysis buffer (50 mM Tris-HCl, pH 7.5, 50 mM 2-mercaptoethanol, 5 mM EGTA, 2 mM EDTA, 1% NP-40, 0.1% sodium dodecyl sulfate polyacrylamide (SDS), 0.5% deoxycholic acid, 10 mM NaF, 1 mM PMSF, 25 mg/ml leupeptin, 2 mg/ml aprotinin). [36] Protein concentrations were determined by Bio-Rad (Richmond, CA, USA) protein assay according to the manufacturer's instructions. Fifty micrograms of total protein from each sample was separated by SDS-PAGE and transferred onto polyvinylidene fluoride membranes using a semidry transfer system from Fisher (Suwanee, GA, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%